Perceptions of ethical decision-making climate among clinicians working in European and US ICUs: differences between religious and non-religious healthcare professionals - Hanne Irene Jensen; Hans-Henrik Bülow; Lucas Dierickx; Stijn Vansteelandt; Rosanna Vaschetto; Gábor Élö; Ruth Piers; Dominique D. Benoit (BMC Medical Ethics)
Abstract Background Making appropriate end-of-life decisions in the intensive care unit (ICU) requires shared interprofessional decision-making. Thus, a decision-making climate that values the contributions of all team members, addresses diverse opinions and seeks consensus among team members is necessary. Little is known about religion’s influence on ethical decision-making climates. Therefore, this study aimed to examine the association between religious belief and ethical decision-making climates. Methods The study was a cross-sectional analytical observation study as a part of the prospective observational DISPROPRICUS study. A total of 2,275 nurses and 717 physicians from 68 ICUs representing 12 countries in Europe and the US participated. All participants were asked which religion (if any) they belonged to and how important their religion (if any) was for their professional attitude towards end-of-life care. Perceptions of ethical decision-making climates were evaluated using a validated, 35-item self-assessment questionnaire that evaluates seven factors. Using cluster analysis, ICUs were categorised into four ethical decision-making climates: good, average (with nurses’ involvement at the end of life), average (without nurses’ involvement at the end of life) and poor. Results Of the 2,992 participants, 453 (15%) were religious (had religious convictions and found them important or very important for their attitude towards end-of-life care). The remaining 2,539 were non-religious (i.e. had religious convictions but assessed that they were not important for their attitude towards end-of-life care). When adjusting for country and ICU, the overall perception of the four ethical climates was associated with religious beliefs, with non-religious healthcare providers having more positive perceptions of the ethical climates compared to religious healthcare providers (p < 0.01). Within good climates, non-religious healthcare providers rated leadership by physicians (p < 0.01), interdisciplinary reflection (p  = 0.049) and active decision-making by physicians (p  = 0.02) as more positive compared to religious participants. In poor climates, religious healthcare providers had a more positive perception of the active involvement of nurses (p = 0.01). Within the other climates, no differences were found. Conclusions Overall perceptions of ethical decision-making climates were associated with religious beliefs, with non-religious healthcare providers generally having a more positive perception of the ethical climates than religious healthcare providers.